2017
DOI: 10.1371/journal.pone.0173843
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in estimated GFR among CKD patients: A 10-year follow-up study of an integrated kidney disease care program in Taiwan

Abstract: BackgroundThis study examined the progression of chronic kidney disease (CKD) by using average annual decline in estimated GFR (eGFR) and its risk factors in a 10-year follow-up CKD cohort.MethodsA prospective, observational cohort study, 4600 individuals fulfilled the definition of CKD, with or without proteinuria, were followed for 10 years. The eGFR was estimated by the MDRD equation. Linear regression was used to estimate participants’ annual decline rate in eGFR. We defined subjects with annual eGFR decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…These factors may explain the fact that this group could maintain their cardiovascular and muscular function and thereby their aerobic ExCap. The mean decline in GFR over time was comparable to or a little lower than values reported in other studies [12,34,35]. Interestingly, Jones et al reported that GFR decline slowed signi cantly following referral to a nephrology clinic, indicating that interventions to slow progression of CKD are important and bene cial.…”
Section: Discussionsupporting
confidence: 68%
“…These factors may explain the fact that this group could maintain their cardiovascular and muscular function and thereby their aerobic ExCap. The mean decline in GFR over time was comparable to or a little lower than values reported in other studies [12,34,35]. Interestingly, Jones et al reported that GFR decline slowed signi cantly following referral to a nephrology clinic, indicating that interventions to slow progression of CKD are important and bene cial.…”
Section: Discussionsupporting
confidence: 68%
“…In 2007, the program used a multidisciplinary approach to focus on CKD stages 3b to 5 (24,25). China Medical University Hospital (CMUH), a tertiary medical center in central Taiwan, joined the program in 2003 and prospectively enrolled consecutive patients with CKD who were willing to participate (25,26). CKD diagnosis was based on the criteria of the National Kidney Foundation Kidney Disease Outcomes Quality Initiative Clinical Practice Guidelines for CKD (25,27).…”
Section: Study Populationmentioning
confidence: 99%
“…Nevertheless, worsening eGFR has been shown to be associated with decreased survival in SCD . Additionally, a growing body of evidence suggests that the rate of annual GFR decline is predictive of progression to ESRD and death in the general population, and that a rapid rate of decline of approximately ≥3 mL/min/1.73 m 2 /year is a useful surrogate measure of clinically meaningful outcomes …”
Section: Introductionmentioning
confidence: 99%